Analisis Data Survival Menggunakan Metode Proportional Hazard dan Accelerated Failure Time - Sri Astuti Thamrin (Jurnal Matematika, Statistika dan Komputasi, 2008)
This paper describes survival data analysis using proportional hazard method and accelerated failure time method to determine the factors that influence survival times of patients’ Diabetes Mellitus in Dr. Wahidin Sudirohusodo hospital in Makassar. Besides that, we compare the results of these methods. The results show that among eight tested variables, three of them are affected factors.